Anatomical correlates of category-selective visual regions have distinctive signatures of connectivity in neonates. (December 2022) - Cabral, Laura; Zubiaurre-Elorza, Leire; Wild, Conor J.; Linke, Annika; Cusack, Rhodri
Abstract: The ventral visual stream is shaped during development by innate proto-organization within the visual system, such as the strong input from the fovea to the fusiform face area. In adults, category-selective regions have distinct signatures of connectivity to brain regions beyond the visual system, likely reflecting cross-modal and motoric associations. We tested if this long-range connectivity is part of the innate proto-organization, or if it develops with postnatal experience, by using diffusion-weighted imaging to characterize the connectivity of anatomical correlates of category-selective regions in neonates (N = 445), 1–9 month old infants (N = 11), and adults (N = 14). Using the HCP data we identified face- and place- selective regions and a third intermediate region with a distinct profile of selectivity. Using linear classifiers, these regions were found to have distinctive connectivity at birth, to other regions in the visual system and to those outside of it. The results support an extended proto-organization that includes long-range connectivity that shapes, and is shaped by, experience-dependent development. Highlights: Anatomical correlates of neonate category-selective regions had mature signatures of structural connectivity. As identified with linear discriminant classifiers, face networks developed early and experienced the least change. Long-range connections to distal regions are part of the innate proto-organization. Category-selective regions were identified by connectivity to the visual system, replicating past proto-organizations.